"I feel that if I didn't come to it anymore, maybe I would go back to my old ways and I don't want that to happen": Adapted sex offender treatment programmes: Views of service users with autism spectrum disorders. Issue 4 (14th July 2019) - Melvin, Clare L.; Langdon, Peter E.; Murphy, Glynis H.
Abstract: Background: The cognitive and behavioural profile associated with autism spectrum disorders (ASD) includes difficulties with social interaction, communication and empathy. Each of these may present barriers to effective participation in sexual offending treatment, leading to poorer outcomes. Method: Semi‐structured interviews were conducted with 13 men with autism and an intellectual disability (including the borderline range) who had completed an adapted sex offender treatment programme. Grounded Theory was used to explore the men's experiences of treatment and perceptions of risk. Results: The men's perceptions of sexual risk were inextricably linked to constructs of identity and shaped their opinions of treatment effectiveness. Risk of reoffending was conveyed through narratives of changes in self and circumstances and included notions of blame and culpability. Conclusions: The findings illustrated some clear benefits for men with ASD associated with attending adapted sex offender treatment programmes, including delivery of treatment within groups and opportunities for social development. The study supports the view that difficulties with empathy and cognitive flexibility complicates treatment for sexual offending.